Entacapone and prostate cancer in Parkinson's disease patients: A large Veterans Affairs healthcare system study. (August 2018) - Major, Jacqueline M.; Dong, Diane; Cunningham, Francesca; By, Kunthel; Hur, Kwan; Shih, David C.; Jiang, Rong; Podskalny, Gerald D.; Wei, XiangMing; Pinheiro, Simone; Bird, Steven T.; Keeton, Stephine; et al.
Abstract: Background: An increased incidence of prostate cancer was observed in Parkinson's disease (PD) patients treated with entacapone during a pre-approval randomized clinical trial; the relation has not been robustly investigated in the U.S. ambulatory setting. Objective: To investigate whether entacapone is associated with prostate cancer and to assess whether the associations are correlated with advanced disease at the time of cancer diagnosis. Methods: Using data from the Department of Veterans Affairs healthcare system, new-user cohorts were created of PD patients treated with add-on entacapone or add-on dopamine agonist/monoamine oxidase B inhibitors between January 2000 and December 2014. Patients were followed on-treatment for occurrence of prostate cancer, identified via linkage to the VA cancer registry. Results: Mean follow-up time was 3.1 and 4.0 years in the entacapone and control cohort, respectively. There were 17, 666 subjects meeting study criteria (mean age, 74 (SD 8.6) years); the entacapone-treated group comprised 5, 257 subjects. Twenty-three prostate cancer cases occurred in the entacapone cohort and ninety-seven in the control cohort. The overall incidence of prostate cancer was 1.8 per 1, 000 person-years of risk. There was no difference in risk of prostate cancer between the cohorts for increased duration of entacapone intake (adjusted HR: 1.08; 95% confidence interval: 0.46–2.51 for cumulative exposure of ≥2 years). Time since starting drug therapy and cumulative dose (mg) also do not suggest a difference in prostate cancer risk between cohorts. Conclusions: Prolonged therapy with entacapone was not associated with increased prostate cancer incidence; however, findings suggest a higher severity of prostate cancer. Highlights: Prolonged entacapone therapy not associated with prostate cancer incidence in cohort study of 17, 666 U.S. male Veterans. Findings suggest more aggressive/advanced cancers at time of cancer diagnosis for entacapone compared to DA/MAOB inhibitors users. Future efforts are needed to further examine risk of advanced prostate cancer.